2022
DOI: 10.1038/s41598-022-07803-2
|View full text |Cite
|
Sign up to set email alerts
|

Povidone iodine suppresses LPS-induced inflammation by inhibiting TLR4/MyD88 formation in airway epithelial cells

Abstract: Povidone-iodine (PVP-I) is an antiseptic and a disinfectant with broad-spectrum antimicrobial activity against various pathogens. However, it is unclear whether PVP-I nasal instillation can suppress mucosal inflammation in non-eosinophilic chronic rhinosinusitis (CRS) mice. This study aimed to explore the anti-inflammatory effects and underlying molecular mechanism of PVP-I on lipopolysaccharide-stimulated airway epithelial cells and investigate whether nasal instillation of PVP-I can suppress mucosal inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…A recent study has revealed the efficacy of nasal irrigation using PVP‐I solution in diminishing secretions among individuals suffering from chronic rhinosinusitis, although the precise mechanism remains unclear 20–22 . In this study, we demonstrated that the utilization of a safe concentration of aqueous solution of PVP‐I, determined through previous experiments, for nasal cavity washing, relieves allergic symptoms and inhibits the activation of IL‐33, which plays an important role in the development of AR 23,24 …”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…A recent study has revealed the efficacy of nasal irrigation using PVP‐I solution in diminishing secretions among individuals suffering from chronic rhinosinusitis, although the precise mechanism remains unclear 20–22 . In this study, we demonstrated that the utilization of a safe concentration of aqueous solution of PVP‐I, determined through previous experiments, for nasal cavity washing, relieves allergic symptoms and inhibits the activation of IL‐33, which plays an important role in the development of AR 23,24 …”
Section: Discussionmentioning
confidence: 62%
“…[20][21][22] In this study, we demonstrated that the utilization of a safe concentration of aqueous solution of PVP-I, determined through previous experiments, for nasal cavity washing, relieves allergic symptoms and inhibits the activation of IL-33, which plays an important role in the development of AR. 23,24 Proteases found in aeroallergens, such as pollens, HDM, and fungi, have the ability to cleave and activate human IL-33FL. 7,25 This process impacts the development of allergic asthma and also correlates with the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the findings of the preceding tests, 2.5 μg/mL curcumin was chosen as the intervention concentration for the following trials. In HNEpC, LPS + ATP promotes inflammation. , The CCK-8 test was used to examine changes in HNEpC cellular viability following 24 h of LPS at various doses paired with 5 mM ATP intervention. Cell viability decreased after LPS intervention at various doses, as seen in Figure b, the CCK-8 assay was used to determine the toxicity of BP-C@PEG and BP to HNEpC (Figure c), after 24 h of coculture with cells, and the materials were tested using the CCK-8 method.…”
Section: Resultsmentioning
confidence: 99%